CONVENTION HOTEL WITH BIOPHILIC DESIGN APPROACH IN SEMARANG CITY - Evelyna, Talitha Zalfa Evelyna; Santoso, Eko Budi; Purnomo, Andi; Savanti, Fisa (Universitas Negeri Semarang, 2024)
The development and construction of Semarang City is increasing with many investors putting in capital or shares in various fields. Various approaches are taken to attract investors and tourists to Semarang City, one of which is by organizing MICE events. Semarang City is one of the 16 cities in Indonesia that has become a MICE destination. However, convention hotel accommodation in one region is still not evenly distributed and there is currently no venue that can accommodate 5,000 people. Therefore, planning and designing a convention hotel in Semarang City is a suitable solution to this problem. The biophilic design approach was considered as an answer to the problem of how hotels contribute to the largest energy use. Therefore, it is necessary to plan and design a convention hotel with a biophilic design concept that fulfills technical aspects, environmentally friendly, and positively impacts human health. This approach prioritizes a building concept that presents the connectivity of residents to the natural environment through the arrangement of interior spaces and landscaping. The design of Convention Hotel with biophilic design approach in Semarang City is used data in the form of primary and secondary data which is then analyzed and processed in functional, contextual, technical, performance, and architectural approaches. By analyzing and processing the data, recommendations and design solutions related to the Convention Hotel with a biophilic design approach in Semarang City will be obtained to support MICE events held in Semarang City.